The Role of Principals’ Transformational Leadership and Kindergarten Organizational Climate in Shaping Teachers’ Work Engagement: The Mediating Effect of Teachers’ Self-Efficacy – Evidence from Jiangsu Province, China - Jing Li; Chonlavit Sutunyarak (Environment and Social Psychology, 2025)
This study examines how principals’ transformational leadership and the kindergarten organizational climate are associated with kindergarten teachers’ work engagement, with a particular focus on the mediating role of kindergarten teachers’ self-efficacy. A survey was conducted with 415 full-time kindergarten teachers across Jiangsu Province, China. Using structural equation modeling (SEM), the relationships among transformational leadership, organizational climate, self-efficacy, and work engagement were tested. The findings show that principals’ transformational leadership is positively associated with teachers’ work engagement. In addition, a positive kindergarten organizational climate, characterized by effective communication and mutual support, is positively associated with kindergarten teachers’ self-efficacy, which in turn is associated with higher work engagement. The results indicate that self-efficacy plays a partial mediating role in the associations between transformational leadership, organizational climate, and teachers’ work engagement. This study extends work on transformational leadership by applying it to Chinese kindergartens and underscores the role of self-efficacy in understanding teacher engagement. It highlights the importance of a supportive environment for strengthening teacher motivation and performance. Practical implications suggest that principals should receive training in emotional intelligence and adaptability, while kindergartens should foster a collaborative climate to help bolster teachers’ self-efficacy and sustain their engagement.